Application of disc spring in clamping force mechanism for electro-mechanical continuously variable transmission - Mazali, Izhari Izmi (Penerbit UTM Press, 2015)
Pulley-based continuously variable transmission (CVT) with metal pushing V-belt (V-belt) offers tremendous potentials in the fuel economy of the car due to its wide and continuous ratio coverage. Nevertheless, the existing pulley-based CVTs in automotive markets use electro-hydro-mechanical (EHM) actuation system to vary its ratio and to provide sufficient clamping force on the V-belt. This, unfortunately, leads to a significant high power consumption from the engine of the car which eventually worsens the car’s fuel economy. To address this issue, researchers introduce electro-mechanical CVT (EM CVT) in which the application of the EHM actuation system is replaced by an electro-mechanical (EM) actuation system. This paper discusses the application of disc spring in clamping force mechanism of EM CVT. The selected disc spring is analyzed and evaluated to prove its workability for CVT’s application. The analysis results indicate that the application of disc spring in clamping force mechanism of EM CVT is possible and it also offers some benefits particularly in term of its compact design.